2018
DOI: 10.1155/2018/1913534
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity, Nutritional Status, and Factors Associated with Malnutrition among People Living with HIV/AIDS Attending Antiretroviral Therapy at Public Health Facilities in West Shewa Zone, Central Ethiopia

Abstract: Background In resource limited settings, HIV/AIDS patients lack access to sufficient nutritious foods, which poses challenges to the success of antiretroviral therapy. HIV/AIDS and malnutrition are still major public health problems in Ethiopia. Though measuring nutritional status is an essential part of ART program, little evidence exists on food insecurity and nutritional status of HIV/AIDS patients in Ethiopia. Hence, the study aimed to determine food insecurity and nutritional status and contextual determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
107
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(142 citation statements)
references
References 34 publications
25
107
4
2
Order By: Relevance
“…Undernutrition was nearly four times and two times more likely among bedridden and ambulatory patients compared to patients who have a working functional status, respectively. Our findings were supported by other studies done in other settings else [6,7,10,11,13,20,21,[24][25][26].…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…Undernutrition was nearly four times and two times more likely among bedridden and ambulatory patients compared to patients who have a working functional status, respectively. Our findings were supported by other studies done in other settings else [6,7,10,11,13,20,21,[24][25][26].…”
Section: Plos Onesupporting
confidence: 93%
“…This is comparable with studies done in different parts of the world [6,7] and Ethiopia [10,21], where undernutrition is more prevalent among the younger adults and overweight is more prevalent among older patients. Additionally, studies also supports the higher proportion of undernutrition among unemployed patients and patients in the lower educational status [11,24,25]. While studies done in Northern and Southern Ethiopia indicated contradicting finding in which undernutrition was higher in older age [11,26].…”
Section: Plos Onementioning
confidence: 77%
“…In Ethiopia, the threat of HIV treatment failure is becoming a continuing discussion. This might be due to poor HIV care services, delayed to recognize treatment failure, [34], late initiation of HAART [33], high burden of opportunistic infections [35], lack of appropriate nutritional support [36], ART-associated adverse reaction, [37] and frequent psychological problem [38,39]. Besides, the absence of frequent therapeutic drug monitors and/ or resistance testing while the patient is still on the suspect or failing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia threat of HIV treatment failure is becoming appointed discussion. This might be due to implementation of poor HIV care, delaying on recognition of symptom of treatment failure, (35), late initiation of HAART (36), high burden of opportunistic infections (37), lack of well nutritional support (38), ART associated adverse reaction, (39) and frequent psychological problem (40,41) are recorded in Ethiopia. Besides, absence of frequent therapeutic drug monitors and/ or resistance testing while the patient is still on the suspect or failing regimen.…”
Section: Discussionmentioning
confidence: 99%